Influence of 16S Ribosomal RNA Gene Polymerase Chain Reaction and Sequencing on Antibiotic Management of Bone and Joint Infections - B Alraddadi; S Al-Azri; KR Forward (Canadian Journal of Infectious Diseases and Medical Microbiology)
INTRODUCTION: Amplification of the 16S ribosomal RNA gene by polymerase chain reaction (PCR) followed by analysis of generated sequences can be an important adjunct to conventional cultures.